Financial Performance Assessment of PT Bumi Resources Tbk in Comparison with other Coal Mining Companies and Estimating the Company Value - Farizan, Radhitya Avila; Soekarno, Subiakto (Journal of Business and Management, 2014)
In the latter half of 2009 until the beginning of 2011, Indonesian coal mining industry experiences an escalation as the increase of global coal mining prices. However from the year 2011 to 2013, coal price is declining. This condition caused by the oversupply of global coal productions. PT Bumi Resources Tbk (BUMI), one of the local mining companies has experienced a downward in the stock price and uncertainties regarding its feature prospect in the long run. This caused by the coal price that significantly decline. From the explanation above, author would like to analyze the company performance and make a comparison with the other local coal mining companies using several methods which are trend analysis, cross-section analysis, common-size financial statement analysis, and DuPont system of analysis. The benchmarking companies are the listed coal mining companies in Indonesia Stock Exchange. From the analysis that has been conducted, the financial performance of PT Bumi Resources Tbk is below the other benchmarking companies caused by several financial issues. Therefore, PT Bumi Resources require improvements to its financial performance to compete with the other coal mining companies. Based on income approach valuation, it indicates that PT Bumi Resources has experienced undervalue. It indicates that PT Bumi Resources Tbk has an opportunity to increase its value. Suggestions that can be given to PT Bumi Resources Tbk are effectively manage the level of debt, to be more effective in using its capital, and consider the cost and operating efficiency in order to improve the financial performance and compete better with the other coal mining companies.Key words: BUMI, financial performance, ratio, valuation